E LEARNING IMPLICATIONS - Usman Arif (International Journal of Contemporary Issues in Social Sciences, 2024)
Conceptualization and Visualization are the implication for e learn in global environments. The digital revolution has brought new concepts which are metaphors that bring myths into realities. The visualization is the data presentation for concepts that shape ideas into theories through experimentation and diagnostic research. Furthermore data abstraction and encapsulation in shaping system designs for contextual studies and scenarios of critical analysis through knowledge management . The core and tacit knowledge shapes the KDDs knowledge systems for conceptual studies. E learn enhances the self learning in generating web casting through web crawlers like search engines of Google to showcase videos and animations of concepts for innovation and Patents. The change can be radicalized through incremental models of learning for knowledge enhancement. Nevertheless neuroticism can be overcome by visual data sets of processor programming for appeals, colors , graphics in podcasts , mobile and tablets making students involvement in learning the new concepts by applying further research in their related field of studies. The research paper is conceptual in nature and the variables like conceptualization and visualization will be further elaborated and can be measured by modal analysis in SPSS for determining e learning through the use of Information communication technologies ICT.